2017
DOI: 10.1160/th17-01-0059
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Progression from Low to High Titres in 260 Children with Severe Haemophilia A and Newly Developed Inhibitors

Abstract: In children with severe haemophilia A, inhibitors to factor VIII (FVIII) usually develop during the first 50 treatment exposure days and are classified as low or high titre depending on the peak inhibitor titre being greater or less than 5 Bethesda units/mL (BU/mL). Classification of the inhibitor may change with time, as some low-titre inhibitors progress to high titre following re-exposure to FVIII concentrate. The aim of this study was to investigate potential risk factors for such a progression in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Some ‘low titre’ inhibitors are transient and will disappear without treatment while others remain or may progress to high titre. Recent data from the PedNet research study group showed that half of the inhibitors to FVIII that were initially classified as ‘low‐titre’ progressed to ‘high titre’ when treated with FVIII (Mancuso et al , ). Today, the development of a ‘high titre’ inhibitor to FVIII or IX is the most serious complication to replacement therapy and renders the patient untreatable with FVIII/IX concentrates.…”
mentioning
confidence: 99%
“…Some ‘low titre’ inhibitors are transient and will disappear without treatment while others remain or may progress to high titre. Recent data from the PedNet research study group showed that half of the inhibitors to FVIII that were initially classified as ‘low‐titre’ progressed to ‘high titre’ when treated with FVIII (Mancuso et al , ). Today, the development of a ‘high titre’ inhibitor to FVIII or IX is the most serious complication to replacement therapy and renders the patient untreatable with FVIII/IX concentrates.…”
mentioning
confidence: 99%
“…Currently, HemA patients who develop FVIII inhibitors undergo ITI protocols to reestablish coagulation potential, with an approximately 70% success rate . Furthermore, it was recently reported that high‐dose ITI is a risk factor for the evolution from low‐titer to high‐titer inhibitors in cohorts of HemA patients and should be avoided as the initial strategy in patients who develop low‐titer FVIII inhibitors. By isolating and selectively expanding FVIII‐sensitized Tregs, the patient’s production of FVIII inhibitors could be reduced or eliminated, eliminating the need for ITI.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is recommended for patients with low-titre inhibitors to avoid the high-dose regimen because of an increased risk of progression to high titre. 8 Here, we analysed risk factors leading to the development of inhibitors in severe haemophilia A PUPs and evaluated the efficacy of the 2 ITI regimens. In the two French centres involved, rFVIII is preferentially used and ITI is initiated as soon as inhibitors are detected.…”
Section: Management Of Previously Untreated Patients With Severe Haemmentioning
confidence: 99%
“…Risk factors to develop inhibitors are similar to those described in other studies and are detailed in Table 1. 1,2,6,9 The first ED occurred at a median age of 11 months (IQR, [6][7][8][9][10][11][12][13][14] and had been initiated following severe bleeding (84.3%), surgery The incidence of FVIII inhibitors in PUPs with severe haemophilia A has been the subject of major publications in recent years 1,4,9,10 which suggest that the use of rFVIII in PUPs makes them at a higher risk of developing inhibitors. The study presented here enrolled all consecutive patients in 2 haemophilic treatment centres that use mostly rFVIII.…”
Section: Management Of Previously Untreated Patients With Severe Haemmentioning
confidence: 99%